Early Hyperchloremia and Outcomes After Severe Traumatic Brain Injury: Analysis of Resuscitation Outcomes Consortium Hypertonic Saline Trial. (5th December 2022) - Qureshi, Adnan I.; Ma, Xiaoyu; Huang, Wei; Nunna, Ravi S.; Gomez, Francisco; Malhotra, Kunal; Arora, Niraj; Chandrasekaran, Premkumar N.; Siddiq, Farhan; Gomez, Camilo R.; Suarez, Jose I.
Abstract : BACKGROUND/OBJECTIVES: To investigate the effect of the occurrence of early hyperchloremia on death or severe disability at 180 days in patients with severe traumatic brain injury (TBI). DESIGN: Post hoc analysis of Resuscitation Outcomes Consortium Hypertonic Saline (ROC HS)-TBI trial. SETTING: A total of 114 North American emergency medical services agencies in the ROC. PATIENTS: A total of 991 patients with severe TBI and Glasgow Coma Scale score of less than or equal to 8. INTERVENTIONS: Prehospital resuscitation with single IV dose (250 cc) of 7.5% saline in 6% dextran-70, 7.5% saline (no dextran), or crystalloid. MEASUREMENTS AND MAIN RESULTS: Patients with increased serum chloride concentrations (110 mmol/L or greater) 24 hours after randomization were identified. Hyperchloremia was graded into one or greater than or equal to 2 occurrences in the first 24 hours. Logistic regression analyses were performed to determine the effects of hyperchloremia on: 1) death or severe disability at 180 days and 2) death within 180 days after adjusting for confounders. Compared with patients without hyperchloremia, patients with greater than or equal to 2 occurrences of hyperchloremia had significantly higher odds of death or severe disability at 180 days (odds ratio [OR], 1.81; 95% CI, 1.19–2.75) and death within 180 days (OR, 1.89; 95% CI, 1.14–3.08) after adjustment for confounders. However, the total volume of fluids administered during the first 24 hours was an independent predictor of death within 180 days; therefore, after adding an interaction term between the total volume of fluids administered during the first 24 hours and greater than or equal to 2 occurrences of hyperchloremia, patients with greater than or equal to 2 occurrences of hyperchloremia had significantly higher odds of death within 180 days (OR, 2.35; 95% CI, 1.21–4.61 d) but not of composite outcome of death or severe disability at 180 days. CONCLUSIONS: After modifying for the effect of the total volume of fluids administered during the first 24 hours, multiple occurrences of hyperchloremia in the first 24 hours were associated with higher odds of death within 180 days in patients with severe TBI.